The economic consequences of supporting organic farms by public funds: case of Poland - Koloszko-Chomentowska, Zofia (Technological and Economic Development of Economy, 2015)
Research proves that the financial support of agriculture is necessary in order to achieve sustainable economic development with other sectors of the economy. The aim of this paper is to assess the economic results of organic farms which benefit from public funds. The research issue was worked out on the basis of the data from organic farms in Podlasie voievodeship in the years 2008–2012. For the purposes of the analysis, farms were divided into area groups: group I – farms with an area up to 20 ha and group II – farms with an area above 20 ha. The following indicators are calculated: family farm income, current ratio, re-investment fixed assets rate, return on equity (ROE). Higher influence of public funds was observed in farms with an area of 20 ha of utilised agricultural area. The income per working person was almost double in larger farms while equity profitability was four times higher than in smaller farms. Only larger farms had the ability to reproduce their used assets. The organic farms realise many important functions in maintenance of the natural environment and so support of these farms by public funds is justified.